DMF-MALDI: droplet based microfluidic combined to MALDI-TOF for focused peptide detection - Kiarach Mesbah (Nature Portfolio, 2017)
Abstract We present an automated droplet microfluidic system (DMF) to generate monitored nanoliter aqueous droplets in oil and their deposition on a commercial stainless steel plate for MALDI-TOF analysis of peptides or protein digests. We demonstrate that DMF-MALDI combination focuses the analyte on the MALDI plate, increasing considerably the homogeneity of the dried material. This results in a 30times enhanced MALDI-TOF MS signal for a model peptide, allowing a significant improvement of the detection sensitivity limit (down to few tens of attomoles). Moreover, positive detection can be achieved from sub-nanomolar peptides solutions and better overall protein sequence coverages are obtained from few tens attomoles of protein digest. These results make DMF-MALDI a promising approach for the treatment of peptides samples as well as a key component for an integrated approach in the proteomic field.